Экологические и биоморфологические особенности видов рода Artemisia L., произрастающих в Украине - Бойко, А.В. (Промышленная ботаника, 2002)
A distribution of Artemisia L. species growing in Ukraine has been carried out to the ecological (with regard of their dependence of the water, light-regime and peculiarities of their trophotope) and to the biomorphologic groups (after general habitus and life-cycle duration, rootage structure, a structure of under- and above-ground shoots and presence of root-stem). These groups are shown to be present irregularly in the subgenera Artemisia L., Dracunculus (Besser) Rydberg and Seriphidium (Besser) Peterm. of the genus under study.